Ventricular fibrillation mechanism and global fibrillatory organisation are determined by gap junction coupling and fibrosis pattern - Handa,B; Li,X; Baxan,N; Roney,C; Shchendrygina,A; Mansfield,C; Jabbour,R; Pitcher,D; Chowdhury,RA; Peters,N; Ng,FS (Cardiovascular Research, 2021)
AimsConflicting data exist supporting differing mechanisms for sustaining ventricular fibrillation (VF), ranging from disorganised multiple-wavelet activation to organised rotational activities (RAs). Abnormal gap junction (GJ) coupling and fibrosis are important in initiation and maintenance of VF. We investigated whether differing ventricular fibrosis patterns and the degree of GJ coupling affected the underlying VF mechanism.Methods and ResultsOptical mapping of 65 Langendorff-perfused rat hearts was performed to study VF mechanisms in control hearts with acute GJ modulation, and separately in three differing chronic ventricular fibrosis models; compact (CF), diffuse (DiF) and patchy (PF). VF dynamics were quantified with phase mapping and frequency dominance index (FDI) analysis, a power ratio of the highest amplitude dominant frequency in the cardiac frequency spectrum.Enhanced GJ coupling with rotigaptide (n = 10) progressively organised fibrillation in a concentration-dependent manner; increasing FDI (0nM: 0.53±0.04, 80nM: 0.78±0.03, p < 0.001), increasing RA sustained VF time (0nM:44±6%, 80nM: 94±2%, p < 0.001) and stabilised RAs (maximum rotations for a RA; 0nM:5.4±0.5, 80nM: 48.2±12.3, p < 0.001). GJ uncoupling with carbenoxolone progressively disorganised VF; the FDI decreased (0µM: 0.60±0.05, 50µM: 0.17±0.03, p < 0.001) and RA-sustained VF time decreased (0µM: 61±9%, 50µM: 3±2%, p < 0.001).In CF, VF activity was disorganised and the RA-sustained VF time was the lowest (CF: 27±7% versus PF: 75±5%, p < 0.001). Global fibrillatory organisation measured by FDI was highest in PF (PF: 0.67±0.05 versus CF: 0.33±0.03, p < 0.001). PF harboured the longest duration and most spatially stable RAs (patchy: 1411&plusm